TRANSPORTATION: THE AGATHOKAKOLOGICAL VEHICLE OF PANDEMIC TRANSMISSION AND MANAGEMENT - Olorunfemi Ayodeji OLOJEDE; Oluwatimilehin Gabriel OLUBORODE (Scientific Journal of Silesian University of Technology. Series Transport)
Discourses on pandemics often prioritize germane pharmaceutical issues while largely ignoring the social dimensions to them, especially the paradoxical role of transportation in pandemic transmission and management. Granted, from an epidemiological perspective, transportation is technically a vector of pandemics; however, by sustaining continuous critical supply chains and facilitating the conveyance of interventions during pandemics, transportation also plays a crucial role in pandemic control and management. Indeed, studies have shown that the risk of disease transmission can be significantly reduced by the observation of non-pharmaceutical transport protocols. Against this background, this paper highlights the dual roles of transportation in aiding and curbing pandemics, with a strong emphasis on the latter. Moreover, towards consolidating on the strengths of the transport sector in the control and management of public health issues, this paper underscores the sacrosanctity of responsible transport. Challenges were identified, and practicable recommendations were proffered towards containing them.